Incidental finding of Taenia saginata during laparotomy for penetrating abdominal trauma by stab wound - Tongale, Ram V.; Khandare , Ravi R. (International Surgery Journal, 2024)
Taenia saginata (T. saginata) is worldwide in distribution. T. saginata has been known as intestinal parasite of man from very ancient times. We report a case of incidental finding of T. saginata during laparotomy for penetrating abdominal trauma by stab wound. The incidental finding of T. saginata during surgery for penetrating abdominal trauma though rare but it accounts for high mortality and morbidity in patients who have penetrating abdominal trauma. It is therefore importance in increasing public knowledge about food hygiene and elimination of worm for better postoperative outcome in patient with abdominal trauma.